Điều khiển tự thích nghi hệ động lực tuyến tính có cấu trúc và thông số không thay đổi - Hưng, Vũ Chấn (Journal of Computer Science and Cybernetics, 2016)
A self-tuning adaptive control algorithm based on the modified variational method and the choosing an appropriate regulator is proposed for system with unknown order and coeeficient.